2013
DOI: 10.1177/1545968313498649
|View full text |Cite
|
Sign up to set email alerts
|

Error Augmentation Enhancing Arm Recovery in Individuals With Chronic Stroke

Abstract: This interactive technology may improve UE motor recovery of stroke-related hemiparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 35 publications
3
92
2
3
Order By: Relevance
“…All included studies, except for one, fell in the definitions we provided a priori for categorizations. Recently, a particular paradigm of HRI (error-augmentation) showed clinical benefits [111], but it did not fit in any of the modalities we described a priori. In this modality, the robot tends to displace the subject’s hand from the optimal trajectory by applying a curl force field to the hand.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies, except for one, fell in the definitions we provided a priori for categorizations. Recently, a particular paradigm of HRI (error-augmentation) showed clinical benefits [111], but it did not fit in any of the modalities we described a priori. In this modality, the robot tends to displace the subject’s hand from the optimal trajectory by applying a curl force field to the hand.…”
Section: Resultsmentioning
confidence: 99%
“…Now that multisession studies with patients have confirmed the usefulness of error augmentation (Abdollahi et al 2014), it is likely to become a stanArticles dard feature of the next generation of commercial rehabilitation robots.…”
Section: Vive La Résistance: Resistive Controlmentioning
confidence: 99%
“…Bu durum motor-hafıza konsolidasyon sürecinin varlığını desteklemektedir (nöroplastisite). Ön çalışmalar hata augmentation stratejisine dayalı öğrenmenin üst ekstremite rehabilitasyonuna ilave edilmesinin kronik inmeli hastalarda faydalı olabileceğini desteklemektedir (3,18,19).…”
Section: S34unclassified